2020
DOI: 10.3389/fgene.2020.01008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cooperative Gene Regulation Among Transcription Factors, LncRNAs, and MicroRNAs in Diabetic Nephropathy Progression

Abstract: The pathogenesis of diabetic nephropathy (DN) is accompanied by alterations in biological function and signaling pathways regulated through complex molecular mechanisms. A number of regulatory factors, including transcription factors (TFs) and non-coding RNAs (ncRNAs, including lncRNAs and miRNAs), have been implicated in DN; however, it is unclear how the interactions among these regulatory factors contribute to the development of DN pathogenesis. In this study, we developed a network-based analysis to deciph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…To prove that, a bioinformatics tool, miRDB ( ) ( Chen & Wang, 2020 ), was applied to predict miRNAs sponged by L13Rik, and 63 candidate miRNAs were identified ( Table S2 ). A previous study demonstrated that 86 miRNAs were dysexpressed in DN progression ( Table S3 ) ( Chen et al, 2020 ). Venn diagram analysis revealed that miR-2861 was the only miRNA that could be sponged by L13Rik and dysregulated in DN patients ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…To prove that, a bioinformatics tool, miRDB ( ) ( Chen & Wang, 2020 ), was applied to predict miRNAs sponged by L13Rik, and 63 candidate miRNAs were identified ( Table S2 ). A previous study demonstrated that 86 miRNAs were dysexpressed in DN progression ( Table S3 ) ( Chen et al, 2020 ). Venn diagram analysis revealed that miR-2861 was the only miRNA that could be sponged by L13Rik and dysregulated in DN patients ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…(Chen and Wang, 2020), was applied to predict miRNAs sponged by L13Rik, and 63 candidate miRNAs were identified (Supporting Table S1). A previous study has demonstrated that 86 miRNAs were dys-expressed in DN progression (Supporting Table S2) (Chen et al, 2020). Venn diagram analysis revealed that miR-2861 was the only miRNA that could be sponged by L13Rik and dy-sregulated in DN patients (Supporting Figure S3).…”
Section: Resultsmentioning
confidence: 95%
“…A few studies have illustrated the role of lncRNA in the development and progression of other diseases through regulation of TFs. Cooperative regulation among two lncRNAs (MALAT1 and NEAT1), three TFs (NF-κB, NFE2L2, and PPARG), and a set of miRNAs has been shown to regulate downstream differentially expressed genes (DEGs) [15]. The lncRNA MAGI2-AS3 has been shown to regulate ACY1 through interaction with the transcription factor HEY1 to prevent tumor growth and angiogenesis in clear cell renal cell carcinoma [16].…”
Section: Introductionmentioning
confidence: 99%